已知函数f(x)=
(Ⅰ)求f′(
(Ⅱ)求证:不等式sin3x>x3cosx在x∈(0,
(Ⅲ)求g(x)=
|
(本小题满分14分)
(Ⅰ)∵f′(x)=
-1=cosx
-sinx(3 cosx
)′3 cosx 3 cos2x
-1=cos3cos2x+sin2x 3cosx 3 cosx
x+2 3
sin2xcos-1 3
x-1…(3分)4 3
∴f′(
)=cosπ 4 2 3
+π 4
sin21 3
cos-π 4 4 3
-1=π 4 2 3
-1…(5分)3 4
(Ⅱ)由(Ⅰ)知f′(x)=cos
x+2 3
sin2xcos-1 3
x-1,其中f(0)=04 3
令G(x)=f'(x),则G′(x)=
cos-2 3
x•(-sinx)+1 3
[2sinxcosxcos-1 3
x+sin2x•(-4 3
)•cos-4 3
x•(-sinx)]7 3
=
sin3xcos-4 9
x>0在x∈(0,7 3
)上恒成立π 2
故G(x)在(0,
)上为增函数,故f′(x)>f′(0)=0,…(8分)π 2
所以f(x)在(0,
)上为增函数,故f(x)>f(0)=0,π 2
即sin3x>x3cosx,…(10分)
(Ⅲ)由(Ⅱ)可知sin3x-x3cosx>0在x∈(0,
]上恒成立.π 4
则g′(x)=
>0在x∈(0,2(sin3x-x3cosx) x3sin3x
]上恒成立. …(12分)π 4
即g(x)在x∈(0,
]单调递增π 4
于是g(x)max=g(
)=2-π 4
…(14分)16 π2